A simple layer-stacking technique to generate biomolecular and mechanical gradients in photocrosslinkable hydrogels. (28th March 2019) - Ko, Hyojin; Suthiwanich, Kasinan; Mary, Héloïse; Zanganeh, Somayeh; Hu, Shu-Kai; Ahadian, Samad; Yang, Yunzhi; Choi, Goro; Fetah, Kirsten; Niu, Yuting; Mao, Jeremy J; Khademhosseini, Ali
Abstract: Physicochemical and biological gradients are desirable features for hydrogels to enhance their relevance to biological environments for three-dimensional (3D) cell culture. Therefore, simple and efficient techniques to generate chemical, physical and biological gradients within hydrogels are highly desirable. This work demonstrates a technique to generate biomolecular and mechanical gradients in photocrosslinkable hydrogels by stacking and crosslinking prehydrogel solution in a layer by layer manner. Partial crosslinking of the hydrogel allows mixing of prehydrogel solution with the previous hydrogel layer, which makes a smooth gradient profile, rather than discrete layers. This technique enables the generation of concentration gradients of bovine serum albumin in both gelatin methacryloyl (GelMA) and poly(ethylene glycol) diacrylate hydrogels, as well as mechanical gradients across a hydrogel containing varying gel concentrations. Fluorescence microscopy, mechanical testing, and scanning electron microscopy show that the gradient profiles can be controlled by changing both the volume and concentration of each layer as well as intensity of UV exposure. GelMA hydrogel gradients with different Young's moduli were successfully used to culture human fibroblasts. The fibroblasts migrated along the gradient axis and showed different morphologies. In general, the proposed technique provides a rapid and simple approach to design and fabricate 3D hydrogel gradients for in vitro biological studies and potentially for in vivo tissue engineering applications.